Designing Community Identity through the Processed Products of Horse Mussel from Ban Bang Chan Conservation Fisheries Group, Takua Thung District, Phang Nga Province - Pinnukul, Patamas; Thongsakul, Rungrat; Hiranphan, Watcharee (Journal of Human and Society, Sisaket Rajabhat University, 2024)
This research had objectives for 1) to study and extract the community identity of the Ban Bang Chan Community, Takua Thung District, Phang Nga Province, and 2) to study the process of designing identity and developing products from horse mussels by the Ban Bang Chan Conservation Fisheries Group in Takua Thung District, Phang Nga Province. This research employed a participatory research design through area context surveys and observations, interviews and satisfaction evaluations which lead to facilitate the extraction of community identity and community identity design through the processed products of horse mussels. The result of the research found out that 1) the community identity consisted of two characteristics: the identity of the natural landscape from the abundant local seafood resource, "horse mussels," that had a great number of it. And the identity of the cultural landscapederived from the community’s way of life, traditional fishing, local knowledge of horse mussel harvesting, and the integration of these identities, which influenced the demand for processed horse mussel products; and 2) the identity design and product development included three-flavor horse mussels, horse mussel crackers, and transformed horse mussel shells for soil conditioning.The design elements included 2.1) geographical place names and product names, 2.2) symbols and logos, 2.3) slogans, 2.4) visual arts reflecting identity, 2.5) typography, and 2.6) distinctive identity, which created an image that aligns with the identity, enhances recognition, attracts attention, and increases the value of community products.